Clinical and experimental Study to evaluate the effect of Biphasic calcium phosphate collagen composite (cpcc) on healing of bone defects after oral surgical procedures - Farha, Liqaa Shallal; Abdulghani, Muhand Munther (AL-Kindy College Medical Journal, 2019)
Background: A recent discoveries used for reconstruction in maxillofacial surgery is the composite bone graft materials. The availability of collagen I matrix make our choice to use this material in surgery .It is biomaterials that its structure could be modified by simple techniques. Studies to find a new materials use for bone reconstruction is to overcome the disadvantages of autogenous bone and the synthetic resorbable bone substitutes.Objectives: This study was done to evaluate the effect of biphasic calcium phosphate collagen composite (ccpc) on healing of bone defects after oral surgical procedures.Type of the study: A cross sectional study.Method: It involved 60 patients, 35 male and 25 female, age (15-40) yearsand experimental animals study involved sixty rabbits.The study was done in Department of Maxillofacial surgery in Al anbarCollege of Dentistry (2015-2016).These patients were received tooth extraction, and other minor surgical procedures .Clinical and radiographical examination and patients consents are done before surgery. The surgery was done under local anesthesia.The resulting bone cavities are filled with composite bone graft material composed from combination of lyophilized hydrolysed collagen sponge (Hemospon),Brasil and Osteon II bone graft material,Korea .The area is closed with 3/0 block silk suture .Antibiotic cover (Ampicillin 500mg ×4) for 1 week was prescribed. The patients were followed up by careful clinical examination with radiograph 15-30 days after surgery. .Sixty New Zeleandi White rabbit were used in our study for histopathologicalexamination.Intraperitoneal injection of ketamine 10 mg with XYL-M2 solution 20 mg xylazine base used to anesthetize the animals. (5mm diameter) bone defects were made using straight surgical hand piece and bur in anterior mandibular region and filled with each material.  The study design involve the following groups: group 1( involve 15 rabbit; the defect was made and filled with blood clot only (control group),group 2( involve 15 rabbit, the defect was made and filled with collagen sponge only),group 3(Involve 15 rabbit, the defect was made and filled with Osteon II bone graft only),group4( involve 15 rabbit, the defect was made and filled with Osteon II bone graft +collagen (Composite bone graft).The flap were closed 3/0 black silk suture. The rabbits were killed after 30 days. 10 cmexcisional biopsy specimen was taken from the paramandibular area and placed in 10%formalin then send histopathologicalexamination.Results:  Clinically, the treated area show good healing with absence of infection .Radiographs during follow up period show radiopacity indicating new bone formation .The results of experimental animals (Rabbits) indicategrowth new bone . In group 1 and group2, the center of the defects was depressed by surrounding tissues  Eung et al, While, in group 3&group 4, the graft materials maintained the space and the center of the defect did not depress. Statistical analysis indicates that during 4 th week ,the highest healing % is (100%) in group 3 &group4 in compared to control group (50%)..A significant difference in healing % was found among the treated groups.Conclusion:The result indicates that biphasic calcium phosphate collagen composite can be efficiently utilized clinically.